SGLT-2 Inhibitors and Renal Outcomes in Non-Diabetic Patients: A Systematic Review - Mariana Silva de Sousa; Cristiana Maia de Almeida; Natália Marchão; Iolanda Godinho; José António Lopes; Joana Gameiro (Publicações Ciência e Vida, 2023)
Introduction: Sodium-glucose cotransporter 2 inhibitors (SGLT2i) have shown positive renal outcomes in diabetic patients. There is also emerging evidence in non-diabetic patients. This review was conducted to analyse the renal outcomes of SGLT2i in patients without diabetes mellitus (DM). Methods: A systematic review was performed in a Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) compliant manner. We included only randomized trials that examined the effect of SGLT2i on renal outcomes in non-diabetic patients. Results: A total of ten randomized trials were included with a combined cohort of 26 298 patients. There was a tendency for lesser risk of adverse renal outcomes in heart failure (HF) patients with reduced ejection fraction (EF) (hazard ratio (HR) 0.50-0.71). Lesser effect on adverse renal outcomes was seen in HF patients with preserved EF (HR 0.95). For both preserved and reduced EF HF, there was a statistically significant reduction in the rate of decline in estimated glomerular filtration rate (eGFR) (p<0.001). On a short follow-up, there was a significant reversible reduction in GFR. In the long term, chronic kidney disease (CKD) proteinuric patients had a statistically significant lesser risk of adverse renal outcomes (p<0.001) and a significant reduction in albuminuria (p=0.0016). CKD patients, including non-proteinuric, had a significant reduction in the rate of kidney disease progression (HR = 0.71). Conclusion: Treatment with SGLT2i significantly reduces the rate of kidney disease progression in CKD non-diabetic patients with eGFR ≥ 20 mL/min/1.73 m2. Benefit seems greater in proteinuric patients. Benefit for eGFR < 20 mL/min/1.73 m2, dialysis and kidney transplant patients is yet to be defined.